The phase equilibrium and density studies of the ternary mixtures of CO2 + Ar + N2 and CO2 + Ar + H2, systems relevance to CCS technology - Ke, Jie; Suleiman, Norhidayah; Sanchez-Vicente, Yolanda; Murphy, Thomas S.; Rodriguez, Javier; Ramos, Alfredo; Poliakoff, Martyn; George, Michael W. (Elsevier, 2017)
The p-T phase diagrams of two ternary systems (CO2 + Ar + N2 and CO2 + Ar + H2) have been measured at temperatures between 268 and 303 K using a fibre-optic phase equilibrium analyser. CO2, which is the major component, has a mole fraction ranging from 0.90 to 0.98 in both systems. The molar ratio of the two minor components is Ar:N2 = 1:1 and Ar:H2 = 2:3, respectively for the two ternary systems. In addition, the density of a ternary mixture with xAr = 0.050 and xN2 = 0.050 is reported at 293.15 K, 303.15 K, 313.15 and 333.15 K and pressures up to 23 MPa. The new experimental phase equilibrium and density data have also been used to evaluate the GERG-2008/EOS-CG, gSAFT and Peng-Robinson equations of state. Among these equations, EOS-CG exhibits the best predictions on both the p-T phase diagrams and densities of CO2 + Ar + N2; and gSAFT gives the lowest average absolute deviation between the predicted and the measured bubble-point pressures of CO2 + Ar + H2.